FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA BERAS DI JAWA TIMUR - Rikawanto Eko Muljawan; Robertus Belarminus Alibaba (Universitas Tribhuwana Tunggadewi, 2009)
Rice strategic position had been important issue since 1998 until 2007. There has been an increasing of rice price, even thought it was slow but sure, at February 2007, which rice price, became the highest price since ever, Rp 6000/kg for medium quality. That increasing of the price are affected by the lack of rice stock in the market in consequence of low rice supply from farmers corresponding to natural disasters and seasonal diversity in some rice production centrals, included East Java province. The production decreasing has an effect on output price became high in proportion to fixed demand. This situation turned out to be worse with the country condition has not been recovered from economic crisis, hence buying power of people turned into low. However, others have not substituted the dependence of the public toward rice at the level of rice as Indonesians’ staple food. This research aims to learn factors influenced rice price in Surabaya city, Malang Region and Sidoarjo Region. The research utilized secondary data during five years since 2002 until 2006 with using linier regression analysis method. Research result shows factors influenced rice price in Surabaya are corn price, cassava price, flour price, and inflation rate; while factors influenced rice price in Malang and corn price, cassava price , and flour price